(untitled) (El-Wahat Journal for Research and Studies, 2015)
The period following the events of September 11, 2001, featured toward Iraq and Iran came in, thanks to preventive war strategy against Iraq and the threat of force against Iran, in order to force them to give up the nuclear program. This is the United States cost a lot of money that was pumped in the wars in Afghanistan and Iraq in particular, led to the US financial crisis that has been moved to the rest of the world. President Obama promised the need to rebuild the US economy from the inside instead of waiting for the financing of wars and compensation of oil from the Gulf. In this context came the requirements of the adoption of the concept of smart power to rebuild the strategic doctrine of the United States, which resulted in the combat withdrawal from Iraq and the signing of the nuclear deal with Iran.